E-Learning Realised By E-Testing - Gushev, Marjan; Armenski, Goce (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2001)
In this paper we introduce an e-Learning upgrade to the current system for online computer-based testing, applied at the PMF Institute of Informatics. This upgrade offers a possibility for the students to attend the lectures online during the school year and at the same time possibility to check their knowledge. The system is build on a well structured organization of the testing questions. It is tree organization with multilevel relations between the database elements. The students are classified according to their study area, and they can attend the lectures only for the subjects they are subscribed to. After attending single lecture, in order to pass to the next one, students have to pass through a test which will show if they have obtained the knowledge from that lecture. The organization of the testing questions implements random positioning of the possible answers that gives possibility not to correlate the question with the answer position instead of learning the essence of the task.
Keywords: Application Service Providers, Internet Service Providers